Time-dependent risk of mortality and end-stage kidney disease among patients with granulomatosis with polyangiitis - Lin, Chun-Yu; Chen, Hung-An; Chang, Tsang-Wei; Hsu, Tsai-Ching; Hsu, Chung-Yuan; Su, Yu-Jih (Frontiers in Medicine, 2022)
Objective To describe the time-dependent impact of granulomatosis with polyangiitis (GPA) on the risk of mortality and end-stage kidney disease (ESKD). The results would provide valuable insight regarding the most vulnerable period for patients with GPA. Methods We conducted a retrospective cohort study using a nationally representative database in Taiwan. Patients with incident GPA without prior ESKD were identified, and non-GPA control cohorts were selected and matched to GPA cohorts based on sex, age, entry time and comorbidities in a 1:4 ratio. Cox regression model was used to estimate hazard ratios (HR) for mortality and ESKD stratified by the follow-up period. Results We identified a total of 142 GPA patients and 568 matched controls. Of those, 52 GPA patients died during follow-up, 48.1% of whom did so within the first 6 months after diagnosis. The 1-, 3-, 5-, and 10-year survival rates of GPA were 78.2, 71.2, 62.6, and 54.7%, respectively. Patients with GPA exhibited the greatest risk of mortality within the first 6 months after follow-up compared with non-GPA cohorts (HR: 21.9, 95% CI: 8.41–57.5). The mortality risk diminished after 1 year and to a marginally significant level during the follow-up period of 5–10 years (HR: 2.71, 95% CI: 0.97–7.62). Ten (7.1%) of the GPA patients experienced ESKD, and these cases occurred exclusively in the first 3 years following diagnosis. Conclusion Our findings suggest that physicians should closely monitor the treatment response and complications of patients with GPA in the first critical 6-month period after diagnosis to improve long-term survival outcome.